Protein-Based Systems for Topical Antibacterial Therapy - Thapa, Raj Kumar; Grønlien, Krister Gjestvang; Tønnesen, Hanne Hjorth (Frontiers in Medical Technology, 2021)
Recently, proteins are gaining attention as potential materials for antibacterial therapy. Proteins possess beneficial properties such as biocompatibility, biodegradability, low immunogenic response, ability to control drug release, and can act as protein-mimics in wound healing. Different plant- and animal-derived proteins can be developed into formulations (films, hydrogels, scaffolds, mats) for topical antibacterial therapy. The application areas for topical antibacterial therapy can be wide including bacterial infections in the skin (e.g., acne, wounds), eyelids, mouth, lips, etc. One of the major challenges of the healthcare system is chronic wound infections. Conventional treatment strategies for topical antibacterial therapy of infected wounds are inadequate, and the development of newer and optimized formulations is warranted. Therefore, this review focuses on recent advances in protein-based systems for topical antibacterial therapy in infected wounds. The opportunities and challenges of such protein-based systems along with their future prospects are discussed.